2020
DOI: 10.3846/jbem.2020.13892
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Performance and Financial Performance Relationship in Banks: Sub-Industry and Cross-Cultural Perspective

Abstract: The aim of the paper is to reveal how corporate social performance (CSP) affects market value and earnings capabilities of companies from banking industry: Banking Services and Investment Banking & Investment Services sub-industries in particular. For Banking Services, the research was extended to a link between corporate social performance and corporate financial performance (CSP-CFP) by classifying institutions into clusters based on a type of culture which dominates in a bank’s country of origin. Regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Further research can be aimed at identifying possible imbalances of interests of various participants in relations with the banking sector and developing proposals for eliminating imbalances, which should be reflected in the banking policy of [72]. In this regard, banks should develop corporate governance, since corporate governance has a positive effect on bank profitability [73], good corporate governance practices improve financial results [74]. The implementation of the principles of responsible banking in the policy of each individual bank will contribute to the sustainable development of the economy and society.…”
Section: Discussionmentioning
confidence: 99%
“…Further research can be aimed at identifying possible imbalances of interests of various participants in relations with the banking sector and developing proposals for eliminating imbalances, which should be reflected in the banking policy of [72]. In this regard, banks should develop corporate governance, since corporate governance has a positive effect on bank profitability [73], good corporate governance practices improve financial results [74]. The implementation of the principles of responsible banking in the policy of each individual bank will contribute to the sustainable development of the economy and society.…”
Section: Discussionmentioning
confidence: 99%
“…While the topic is widely described with regard to CSR issues, it is still rarely addressed in the area of ESG issues and has not yet been developed in the relatively new Green Deal approach. However, it is still possible to identify a relatively small number of publications addressing the links between the financial efficiency of institutions and the implementation of ESG measures, in which the environmental dimension is one of many analysed in the banking sector (Soana, 2011;Paulík et al, 2015;Huang et al, 2017;Daszyńska-Żygadło et al, 2021;Klimontowicz et al, 2021;Bose et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results are surprisingly mixed. In certain cases, governance positively influences financial performance (Daszyńska-Żygadło et al, 2021;Esteban-Sanchez et al, 2017;Khattak, 2021) while in other instances, governance did not affect financial performance (Dragomir et al, 2022;La Torre et al, 2021;Shakil et al, 2019). Further, four studies found that governance only influenced certain aspects of bank financial performance, or paradoxically, was negatively associated with financial performance (Azmi et al, 2021;El Khoury et al, 2023;Menicucci & Paolucci, 2023;Rahi et al, 2021).…”
Section: Research On the Governance Quality -Financial Performance Ne...mentioning
confidence: 99%
“…This literature affirms a positive association between ALM and financial performance. Other studies have documented the relationship between bank governance quality and financial performance measures such as ROA or ROE, with mixed outcomes (Azmi et al, 2021;Daszyńska-Żygadło et al, 2021;Dragomir et al, 2022;El Khoury et al, 2023;Esteban-Sanchez et al, 2017;Khattak, 2021;La Torre et al, 2021;Rahi et al, 2021;Shakil et al, 2019). However, Fernandes et al (2018) observed that empirical research related to the nexus of bank governance quality and financial performance has ignored ALM.…”
Section: Introductionmentioning
confidence: 99%